Cumulative Vulnerability: A Case Study on intrafamilial violence, Drug Addiction and Adolescent Pregnancy - Miura, Paula Orchiucci; Passarini, Gislaine Martins Ricardo; Ferreira, Loraine Seixas; Paixão, Rui Alexandre Paquete; Tardivo, Leila Salomão de La Plata Cury; Barrientos, Dora Mariela Salcedo (Revista da Escola de Enfermagem da USP, 2014)
A pregnant adolescent’s vulnerability increases when she is a victim of intrafamilial violence and drug addiction, which cause physical and biopsychosocial damage to the mother and her baby. Objective Present and analyze the case of an adolescent who is addicted to drugs, pregnant and the victim of lifelong intrafamilial violence. Method A case study based on a semi-structured interview conducted in the Obstetrics Emergency Unit at the Teaching Hospital of the University of São Paulo. The data were interpreted and analyzed using Content Analysis. Results intrafamilial violence experienced at the beginning of the adolescent’s early relationships seriously affected her emotional maturity, triggering the development of psychopathologies and leaving her more susceptible to the use and abuse of alcohol and other drugs. The adolescent is repeating her history with her daughter, reproducing the cycle of violence. Conclusion Adolescent pregnancy combined with intrafamilial violence and drug addiction and multiplies the adolescent’s psychosocial vulnerability increased the adolescent’s vulnerability.